Problematic questions of software requirements engineering training (Educational Dimension, 2021)
The key problems of training Requirement Engineering and the following ways to overcome the contradiction between the crucial role of Requirement Engineering in industrial software development and insufficient motivation to master it in the process of SE specialists professional training were identified based on a systematic research analysis on the formation of the ability of future software engineering (SE) specialists to identify, classify and formulate software requirements: use of activity and constructivist approaches, game teaching methods in the process of modeling requirements; active involvement of stakeholders in identifying, formulating and verifying requirements at the beginning of the project and evaluating its results at the end; application of mobile technologies for training of geographically distributed work with requirements; implementation of interdisciplinary cross-cutting projects on SE; involvement of students in real projects; stimulating the creation of interdisciplinary and age-old student project teams.